Quantitative easing and the supply of safe assets: Evidence from international bond safety premia - Jens H. E. Christensen; Nikola Mirkov; Xin Zhang (Sveriges Riksbank, 2024)
Through large-scale asset purchases, widely known as quantitative easing (QE), central banks around the world have affected the supply of safe assets by buying quasi-safe bonds in exchange for truly safe reserves. We examine the pricing effects of the European Central Bank's bond purchases in the 2015-2021 period on an international panel of bond safety premia from four highly rated countries: Denmark, Germany, Sweden, and Switzerland. We find statistically significant negative effects for all four countries. This points to an important international spillover channel of QE programs to bond safety premia that operates by increasing the amount of truly safe assets.
Keywords: E43; E47; G12; G13; F42; 330; term structure modeling; convenience yields; unconventional monetary policy; European Central Bank